Kajian terhadap Tradisi Mohatu Suku Saluan di Desa Simpang II dari Perspektif Teologi Kristen - Bungalan, Jhon Efrendi; Pasande, Purnama; Ruindungan, Leo Mardani; Parinsi, Niel (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
This paper aims to examine from the perspective of Christian theology the Mohatu tradition, which is still practiced among the Saluan tribe in Simpang II village. The Mohatu tradition is a ritual for releasing the spirits of the dead, carried out 16 days after death, by placing seven to nine types of garden produce on the deceased's grave. Then the spirits will no longer come to collect garden produce which can result in crop failure. The research method is ethnography, with in-depth interviews as a data collection technique. Data were analyzed with reduction, display, and conclusion techniques. The informants involved totaled 15, consisting of traditional leaders and community leaders of the Saluan tribe, as well as Pastors and Congregational Councils who serve in the Saluan tribe. The study results show that the Mohatu tradition is a medium for the Saluan tribe to deal with farmers' crop failures. In the Mohatu tradition, spirits are believed to remain in the world (graves) and carry out their usual activities, including gardening. Because of that, the spirits can still interfere with plantation activities. This tradition needs to be transformed because it has the potential to slow down the development and use of agricultural technology by the Saluan people. Transformation is possible with a religious approach through contextualizing Christian theology about death. In Christian theology, God has power over life and death. After humans die physically, their spirits will return to God, so no more spirits in this world can affect human life.